A Comparative Investigation of Communication Apprehension among Undergraduate, Graduate, and Postgraduate Students in the EFL Context - Ulfah, Badriyah (IJELTAL (Indonesian Journal of English Language Teaching and Applied Linguistics), 2024)
Communication Apprehension (CA) is a pervasive challenge that significantly affects students, particularly those pursuing higher education in an English as a Foreign Language (EFL) context. This study serves a threefold purpose: (1) to quantify and compare the levels of CA experienced by students across different EFL educational levels, (2) to investigate potential relationships between students' CA and their educational backgrounds, and (3) to explore the strategies students employ to overcome CA. A survey research design involving 60 EFL students from three distinct cohorts (24 undergraduates, 16 graduates, and 20 postgraduates) was conducted using a convenience sampling technique. Data were collected utilizing McCroskey's Personal Report of CA (PRCA-24, 2005) and analyzed using descriptive and correlational statistics via the SPSS software. The results reveal that all undergraduates (100%), a substantial proportion of graduates (68.75%), and a notable fraction of postgraduates (45%) experienced an average level of CA, with public speaking situations being the most common triggers. While a weak negative correlation was identified (-0.225), it did not attain conventional statistical significance (sig 0.084). Furthermore, students adopt cognitive, behavioural, and preparatory strategies to manage CA effectively. This research underscores the importance of identifying specific communication situations in which students experience heightened apprehension, facilitating the development of targeted interventions to address their unique needs in these areas